The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/diagnostics14010013
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach for Improved Longitudinal Prediction of Progression from Mild Cognitive Impairment to Alzheimer’s Disease

Robert P. Adelson,
Anurag Garikipati,
Jenish Maharjan
et al.

Abstract: Mild cognitive impairment (MCI) is cognitive decline that can indicate future risk of Alzheimer’s disease (AD). We developed and validated a machine learning algorithm (MLA), based on a gradient-boosted tree ensemble method, to analyze phenotypic data for individuals 55–88 years old (n = 493) diagnosed with MCI. Data were analyzed within multiple prediction windows and averaged to predict progression to AD within 24–48 months. The MLA outperformed the mini-mental state examination (MMSE) and three comparison m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Many existing studies focused on using AI techniques to predict later stage of cognitive decline 7,9,[32][33][34] . A few studies were about NLP techniques for detecting cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Many existing studies focused on using AI techniques to predict later stage of cognitive decline 7,9,[32][33][34] . A few studies were about NLP techniques for detecting cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…We think that a combination of strategies can be employed to further improve model performance with the end goal of developing practical and accessible tools that can be utilized in real-world clinical scenarios to provide additional resources for physicians, therefore enabling better health outcomes for patients. Furthermore, we think that integrating LLM capabilities with other medical AI algorithms, which already show promise in diagnostics and treatment delivery 37 , 38 , for example can provide for extremely powerful yet accessible tools that present the additional advantage of ease of implementation in healthcare workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning can encompass various clinical data, not just MRI data. Previous research has utilised cognitive data, activity of daily living, and behavioural and psychological symptoms of dementia to differentiate between MCI and Alzheimer's disease (AD) through machine learning [13], and diverse biomarkers and clinical data have been employed to predict the prognosis of MCI through machine learning [14]. Additionally, studies using physiological data from wearable devices have shown results in predicting cognitive function in MCI [15].…”
Section: Introductionmentioning
confidence: 99%